Effect of Pregnancy Duration on the Levels of Some Biochemical Parameters in Pregnant Women - Issa, Najlaa (University of Thi-Qar Journal of Science, 2010)
The study investigated the effect of pregnancy case on the level of some biochemical components in the blood sera, which accompany fetus growth of. It was conducted on (45) blood serum of pregnant women and compared with (52) blood serum of non-pregnant women which were considered as control group. The measured parameters in sera were included the electrolyte (sodium and potassium) and some trace element (selenium) as well as the antioxidant vitamins (A, C, E). The results showed non-significant decrease in (sodium and potassium) concentrations of pregnant women compared with control group, while a significant decrease in level of selenium was noticed in serum of pregnant women compared with control group. The results also showed a significant decrease in the levels of vitamins (A , C , E) in serum of pregnant women compared with control group. An inverse relationship between the concentration of determined vitamins E and C during pregnancy period .It was noted that vitamin E concentration decreased, and that of vitamin Cincreased during pregnancy period.